Coccolith malformation in the Aegean Sea - Dimiza, M.; Triantaphyllou, M.; Krasakopoulou, E. (Scientific Annals of the School of Geology, 2012)
Ocean acidification and the related changes in seawater chemistry may disrupt calcification by coccolithophores and departure from the normal growth process causing malformed coccoliths. Coccospheres with malformed were coccoliths collected from different locations in the Aegean Sea. Although most of these specimens in our work are restricted to Emiliania huxleyi, scarce coccospheres of Rhabdosphaera clavigera, Syracosphaera pulchra, Discosphaera tubifera and Calcidiscus quadriperforatus have also been detected. In this study we discuss our observations on malformed distribution in relation to seawater carbonate chemistry.